Anthropological Dimension of the Artistic Creations of Krystyna Herling-Grudziński - Bielska-Krawczyk, Joanna (Roczniki Kulturoznawcze, 2011)
The main goal of this article is to reveal anthropological dimention of the artistic creations of almost unknown painter, the wife of the outstanding polish writer Gustaw Herling-Grudziński – Krystyna Herling-Grudziński. In the text I ask questions about the vision of a human being that we can find in those pictures and the ways painter shows its depersonalization. The main motivation of the use of anthropological perspective in the study of those works is biography of the artist (especially her suicidal death) and the character of her creations.